Integrated molecular genetic profiling of pediatric high-grade gliomas reveals key differences with the adult disease - Paugh, Barbara S; Qu, Chunxu; Jones, Chris; Liu, Zhaoli; Adamowicz-Brice, Martyna; Zhang, Junyuan; Bax, Dorine A; Coyle, Beth; Barrow, Jennifer; Hargrave, Darren; Lowe, James; Gajjar, Amar; et al. (Journal of clinical oncology, 2010)
To define copy number alterations and gene expression signatures underlying pediatric high-grade glioma (HGG). We conducted a high-resolution analysis of genomic imbalances in 78 de novo pediatric HGGs, including seven diffuse intrinsic pontine gliomas, and 10 HGGs arising in children who received cranial irradiation for a previous cancer using single nucleotide polymorphism microarray analysis. Gene expression was analyzed with gene expression microarrays for 53 tumors. Results were compared with publicly available data from adult tumors. Significant differences in copy number alterations distinguish childhood and adult glioblastoma. PDGFRA was the predominant target of focal amplification in childhood HGG, including diffuse intrinsic pontine gliomas, and gene expression analyses supported an important role for deregulated PDGFRalpha signaling in pediatric HGG. No IDH1 hotspot mutations were found in pediatric tumors, highlighting molecular differences with adult secondary glioblastoma. Pediatric and adult glioblastomas were clearly distinguished by frequent gain of chromosome 1q (30% v 9%, respectively) and lower frequency of chromosome 7 gain (13% v 74%, respectively) and 10q loss (35% v 80%, respectively). PDGFRA amplification and 1q gain occurred at significantly higher frequency in irradiation-induced tumors, suggesting that these are initiating events in childhood gliomagenesis. A subset of pediatric HGGs showed minimal copy number changes. Integrated molecular profiling showed substantial differences in the molecular features underlying pediatric and adult HGG, indicating that findings in adult tumors cannot be simply extrapolated to younger patients. PDGFRalpha may be a useful target for pediatric HGG, including diffuse pontine gliomas.